Effect of aeration and agitation on extractive fermentation of clavulanic acid by using aqueous two-phase system - Viana Marques, Daniela A.; Santos-Ebinuma, Valéria C. [UNESP]; Pessoa-Júnior, Adalberto; Porto, Ana L. F.; Torres, Beatriz Rivas; Converti, Attilio (Wiley, 2016)
In this work, the effects of agitation and aeration rates on aqueous two-phase system (ATPS)-based extractive fermentation of clavulanic acid (CA) by Streptomyces variabilis DAUFPE 3060 were investigated through a 22 full factorial design, where oxygen transfer rate (OTR) and oxygen uptake rate (OUR) were selected as the responses. Aeration rates significantly influenced cell growth, OUR, and CA yield, while OTR was practically the same in all the runs. Under the intermediate agitation (950 rpm) and aeration conditions (3.5 vvm) of the central point runs, it was achieved OTR of 1.617 ± 0.049 mmol L−1 h−1, OUR of 0.132 ± 0.030 mmol L−1 h−1, maximum CA production of 434 ± 4 mg L−1, oxygen mass transfer coefficient of 33.40 ± 2.01 s−1, partition coefficient of 66.5 ± 1.5, CA yield in the top and bottom phases of 75% ± 2% and 19% ± 1%, respectively, mass balance of 95% ± 4% and purification factor of 3.8 ± 0.1. These results not only confirmed the paramount role of O2 supply, broth composition and operational conditions in CA ATPS-extractive fermentation, but also demonstrated the possibility of effectively using this technology as a cheap tool to simultaneously produce and recover CA. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1444–1452, 2016.
Keywords: aqueous two-phase system; bioprocess; clavulanic acid; extractive fermentation; oxygen transfer